Aortopathy and bicuspid aortic valve: haemodynamic burden is main contributor to aortic dilatation. Issue 24 (30th November 2012) - Kim, Yong-Giun; Sun, Byung Joo; Park, Gyung-Min; Han, Seungbong; Kim, Dae-Hee; Song, Jong-Min; Kang, Duk-Hyun; Song, Jae-Kwan
Abstract : Objective: To evaluate factors associated with aortic enlargement in patients with a bicuspid aortic valve (BAV) and the impact of isolated aortic valve replacement (AVR). Design and setting: A retrospective analysis of clinical data in a tertiary referral hospital. Patients and main outcome measures: We performed a cross-sectional analysis of 595 patients with BAV to assess variables determining maximal ascending aortic dimension. To measure annual dilatation rates, baseline and follow-up echocardiograms were analysed in 70 patients with BAV (BAV-AVR group) and 48 with a tricuspid aortic valve (TVA-AVR group) who underwent isolated AVR, and compared with 65 patients with BAV who did not undergo AVR (BAV-NAVR group). Results: Aortic regurgitation (AR) severity was associated with aortic sinus diameter (p<0.001), whereas aortic stenosis severity with the tubular diameter (p<0.001). Multivariate analysis showed that age was an independent factor for both sinus and tubular diameter with AR severity being for aortic sinus diameter and moderate to severe aortic stenosis or AR being for aortic tubular diameter. Despite younger age and lower prevalence of moderate to severe valvular dysfunction at baseline, the annual dilatation rates at sinus and tubular part were significantly higher in the BAV-NAVR than in the BAV-AVR and TAV-AVR groups (p<0.05 each), which did not differ in the BAV-AVR and TAV-AVR groups (p=0.402 for sinus and p=0.394 for tubular part). Conclusions: Age-dependent aortic enlargement associated with significant valvular dysfunction and the protective effects of isolated AVR in patients with BAV indicate that valvular dysfunction is a major determinant to the development of aortopathy.